2010
DOI: 10.1007/s11517-010-0620-3
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension values of cerebral and cerebellar activity in rats loaded with aluminium

Abstract: Aluminium interferes with a variety of cellular metabolic processes in the mammalian nervous system and its intake might increase a risk of developing Alzheimer's disease (AD). While cerebral involvement even at the early stages of intoxication is well known, the role of cerebellum is underestimated. Our aim was to investigate cerebral and cerebellar electrocortical activity in adult male rats exposed to chronic aluminium treatment by nonlinear analytic tools. The adult rats in an aluminium-treated group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the study by Spasić (2005Spasić ( -2010 [13,14] the HFD method was first applied to calculate fractal dimension of EEG signal in rats with injury to the brain. Kekovic et al [15] described a mechanism of the development of Alzheimer's disease having established a diffuse neurotoxic effect of chemicals on rats' brains by the HFD method of calculating.…”
Section: Clinical Supplementsmentioning
confidence: 99%
“…In the study by Spasić (2005Spasić ( -2010 [13,14] the HFD method was first applied to calculate fractal dimension of EEG signal in rats with injury to the brain. Kekovic et al [15] described a mechanism of the development of Alzheimer's disease having established a diffuse neurotoxic effect of chemicals on rats' brains by the HFD method of calculating.…”
Section: Clinical Supplementsmentioning
confidence: 99%
“…Particularly, an increase in the delta range is an indicator of neurotoxicity, while change in the delta/theta relation is a criterion of intoxication [18]. The FD of electrocortical activity during neurotoxicity has a lower value [19]. The change in FD of electrocortical activity in anesthetized rats and those treated with aluminium, describes rhythm desynchronization.…”
Section: Discussionmentioning
confidence: 99%
“…Kekovic et al also utilized Higuchi's algorithm of fractal analysis to investigate the brain activity in 10 rats given aluminum and 10 control rats. This study attempted to determine the effects of aluminum in the cerebrum and cerebellum and found that aluminum diminishes electrocortical activity in the cerebral hemispheres only (Kekovic et al, 2010a). While these effects may not necessarily be the same in humans, the promising ability of FD to discriminate the efficacy of the drugs suggests that fractal analysis can also be used to determine the effects of various doses of drugs on the brains of patients.…”
Section: Neuropharmacologymentioning
confidence: 99%